2008
DOI: 10.1007/s00259-008-0776-3
|View full text |Cite
|
Sign up to set email alerts
|

Performance of integrated FDG–PET/contrast-enhanced CT in the diagnosis of recurrent ovarian cancer: comparison with integrated FDG–PET/non-contrast-enhanced CT and enhanced CT

Abstract: Integrated PET/contrast-enhanced CT is an accurate modality for assessing ovarian cancer recurrence and led to changes in the subsequent appropriate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 34 publications
2
64
4
Order By: Relevance
“…These data are further confirmed by Kitajima and colleagues in a series of studies in patients with uterine, ovarian, colorectal and pancreas cancer [8][9][10][11][12][13].…”
Section: Contrast-enhanced Studies With Pet/ct Hybrid Camerassupporting
confidence: 65%
“…These data are further confirmed by Kitajima and colleagues in a series of studies in patients with uterine, ovarian, colorectal and pancreas cancer [8][9][10][11][12][13].…”
Section: Contrast-enhanced Studies With Pet/ct Hybrid Camerassupporting
confidence: 65%
“…In the prior studies, researchers found that accuracy, sensitivity, and specifi city were 63%-100%, 73%-100%, and 40%-100%, respectively, at the patient level and 72%-96%, 41%-78%, and 75%-99%, respectively, at the region level ( 14,16,17,20,(25)(26)(27)(28)(29)(30). In these prior studies, the diagnostic The number, size (on CE CT and PET/CT images) and SUV max (on PET/CT images) of peritoneal deposits (for all three readers) and of distant (M1) lymph node metastases (readers 1 and 2 only) were signifi cantly associated with poor survival ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…A lymph node was considered suspicious for malignancy on a CE CT image if it measured 7 mm or longer in the short-axis diameter. This approach to image analysis was based on the experience of the authors, review of the published literature, and the institution's surgical template ( 4,(7)(8)(9)14,21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For ovarian cancer, both sensitivity and specificity in detecting PM is in the range of 78 %-97 %. [28][29][30][31][32][33] A recent metaanalysis of imaging modalities for recurrent ovarian cancer showed that PET-CT had the highest pooled sensitivity of 92 %,compared with PET,CT or MRI alone [34].…”
Section: Positron Emission Tomography (Pet) Scan and Pet-ctmentioning
confidence: 99%